Geonetdigitizer: Open source code to digitalize information given in Wulff and Lambert nets (2015)
The article carries out the theoretical basis, the usefulness, and validation of the computational program geonetDigitizer (licensed as an open-source code as BSD-2) in order to apply as a toolbox for the programming language MATLAB©. The program geonetDigitizer was designed for the digitalization of plots expressed in the spherical projections Wulff and Lambert, which is of extensive use in structural geology and geomechanics. The reasons of presenting the program as an open code has the purpose to recover historical data presented in those projections, as also to recover old and modern information presented in that projections. All of these will reduce the possible phenomenon known as Digital Dark Age. To validate the code, it is presented here two examples, where real known values are compared with their corresponding values obtained by the process of digitizing. Finally, in the appendix is presented two application examples.